The kinetics of polyurethane structural foam formation: Foaming and polymerization. Issue 7 (1st March 2017) - Rao, Rekha R.; Mondy, Lisa A.; Long, Kevin N.; Celina, Mathew C.; Wyatt, Nicholas; Roberts, Christine C.; Soehnel, Melissa M.; Brunini, Victor E.
Abstract : Kinetic models have been developed to understand the manufacturing of polymeric foams, which evolve from low viscosity Newtonian liquids, to bubbly liquids, finally producing solid foam. Closed‐form kinetics are formulated and parameterized for PMDI‐10, a fast curing polyurethane, including polymerization and foaming. PMDI‐10 is chemically blown, where water and isocyanate react to form carbon dioxide. The isocyanate reacts with polyol in a competing reaction, producing polymer. Our approach is unique, although it builds on our previous work and the polymerization literature. This kinetic model follows a simplified mathematical formalism that decouples foaming and curing, including an evolving glass transition temperature to represent vitrification. This approach is based on IR, DSC, and volume evolution data, where we observed that the isocyanate is always in excess and does not affect the kinetics. The kinetics are suitable for implementation into a computational fluid dynamics framework, which will be explored in subsequent articles. © 2017 American Institute of Chemical Engineers AIChE J, 63: 2945–2957, 2017